2012
DOI: 10.4085/1062-6050-47.5.03
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorder Risk and the Role of Clothing in Collegiate Cheerleaders' Body Images

Abstract: Cheerleaders, especially flyers, appear to be at risk for EDs, with greatest BI dissatisfaction when wearing their most revealing uniforms (ie, midriffs). Universities, colleges, and the national governing bodies of these squads need to focus on preventing eating disorders and BI dissatisfaction and promoting self-esteem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
29
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 25 publications
6
29
6
Order By: Relevance
“…The major finding was that both wearing revealing clothes and wearing tight-fitting clothes were contextual cues that could result in increased state self-objectification, and wearing tight-fitting revealing clothes could occasionally trigger greater state self-objectification than wearing revealing loose clothes and full tight-fitting clothes. Besides, our results-that wearing revealing clothes led to significantly greater state self-objectification than wearing full clothes-corroborates the argument about the role of wearing revealing clothes on self-objectification [4] [9]. The phenomenon that both wearing tight-fitting clothes and revealing clothes can trigger and increase self-objectification and body surveillance may rely on two pathways.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The major finding was that both wearing revealing clothes and wearing tight-fitting clothes were contextual cues that could result in increased state self-objectification, and wearing tight-fitting revealing clothes could occasionally trigger greater state self-objectification than wearing revealing loose clothes and full tight-fitting clothes. Besides, our results-that wearing revealing clothes led to significantly greater state self-objectification than wearing full clothes-corroborates the argument about the role of wearing revealing clothes on self-objectification [4] [9]. The phenomenon that both wearing tight-fitting clothes and revealing clothes can trigger and increase self-objectification and body surveillance may rely on two pathways.…”
Section: Discussionsupporting
confidence: 84%
“…American female collegiate cheerleaders reported that they experienced most body dissatisfaction when wearing most revealing uniforms compared to wearing daily clothing and full uniforms[9]. Similarly, in an American female collegiate dancers' sample and an American female collegiate equestrian athletes'…”
mentioning
confidence: 90%
“…First, misconceptions of body size and weight might be differential and reporting bias, for example by sex, education and overweight (27) or due to psychiatric disorders (28) , cannot be totally excluded. Therefore, at the individual level, there is a risk of misclassification when using figural scales.…”
Section: Discussionmentioning
confidence: 99%
“…Cheerleaders perform high-impact gymnastics based movements, while pep dancers perform routines based on low-impact hip hop and ballet dance movements. Although the National Collegiate Athletic Association (NCAA) does not recognize dancing and cheerleading as sports [14], research has shown that both activities require similar physical demands as other collegiate sports based on the results of various fitness tests [15,16]. Participants in both cheer and dance have also shown a high prevalence of disordered eating and pressure to be thin when compared with other sports [17], as well as high prevalence of vitamin D insufficiency [18][19][20], which could potentially have detrimental effects on their bone health.…”
mentioning
confidence: 99%